2022
DOI: 10.1242/jcs.260120
|View full text |Cite
|
Sign up to set email alerts
|

A new mechanism of fibronectin fibril assembly revealed by live imaging and super-resolution microscopy

Abstract: Fn1 fibrils have long been viewed as continuous fibers composed of extended, periodically aligned Fn1 molecules. However, our live imaging and single-molecule localization microscopy (SMLM) are inconsistent with this traditional view and show Fn1 fibrils composed of roughly spherical nanodomains containing 6-11 Fn1 dimers. As they move toward the cell center, Fn1 nanodomains become organized into linear arrays, wherein nanodomains are spaced at the average periodicity of 105±17 nm. Periodical Fn1 nanodomain ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

5
1

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 98 publications
2
10
0
Order By: Relevance
“…In line with this notion, we found that in cultured cells expressing GFP-tagged FN 24 , FN fibrils are observed under β1-integrin adhesions and LoxL3 is distributed at nascent adhesion sites (Figure 1A). Notably, LoxL3 is expressed in neural crest cells (Figure S1A) and following its deletion (LoxL3 Δ/Δ ) the mutant embryos display a cleft palate phenotype and reduced neural crest cell numbers at branchial arches (Figure S1B-H), both of which are FN-associated phenotypes 25,26 .…”
Section: Lysyl Oxidases Promote Fn Fibrillogenesis and Cell Spreading...supporting
confidence: 78%
See 2 more Smart Citations
“…In line with this notion, we found that in cultured cells expressing GFP-tagged FN 24 , FN fibrils are observed under β1-integrin adhesions and LoxL3 is distributed at nascent adhesion sites (Figure 1A). Notably, LoxL3 is expressed in neural crest cells (Figure S1A) and following its deletion (LoxL3 Δ/Δ ) the mutant embryos display a cleft palate phenotype and reduced neural crest cell numbers at branchial arches (Figure S1B-H), both of which are FN-associated phenotypes 25,26 .…”
Section: Lysyl Oxidases Promote Fn Fibrillogenesis and Cell Spreading...supporting
confidence: 78%
“…Cell culture: MEF FN-GFP were described previously 24 Adhesion, cell area and fibronectin analysis: All of the adhesion and fibronectin fibrils analyses shown in this paper were performed using the trainable Weka segmentation plugin 45 of ImageJ (NIH) software.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet for the two optimized strategies we tested here, 2-color SD-STORM is not slower than S2C-PAINT, because the loss in maximum density is more than compensated by the faster blinking and lower exposure times possible with STORM compared to PAINT. For 2-color acquisitions, we thus would favor SD-STORM over S2C-PAINT as it is compatible with initial observation before super-resolved acquisition, faster, straightforward to implement with a commercially available setup (Jackson et al, 2022; Tomer et al, 2022; Gazzola et al, 2023) and readily extensible to 3-color imaging. A key advantage of S2C-PAINT in the future is that implementing successive rounds of PAINT imaging would provide a straightforward way to extend it to multiplexing with 4 or more channels, with a significant gain in speed compared to single-color Exchange PAINT.…”
Section: Discussionmentioning
confidence: 99%
“…Yet for the two optimized strategies we tested here, two-color SD-dSTORM is not slower than S2C-DNA-PAINT, because the loss in maximum density is more than compensated by the faster blinking and lower exposure times possible with dSTORM compared with DNA-PAINT ( Table S1 ). For two-color acquisitions, we thus would favor SD-dSTORM over S2C-DNA-PAINT as it is compatible with initial observation before super-resolved acquisition, faster, straightforward to implement with a commercially available setup, 56 , 57 , 58 and readily extensible to three-color imaging. A key advantage of S2C-DNA-PAINT in the future is that implementing successive rounds of PAINT imaging would provide a straightforward way to extend it to multiplexing with four or more channels, with the possibility of combining it with recent faster DNA-PAINT approaches 16 , 59 for a significant gain in speed compared with single-color exchange-PAINT.…”
Section: Discussionmentioning
confidence: 99%